Odpowiedzi

2009-11-28T16:08:16+01:00
A)
4x(x-2)= (2x+4)²
4x² - 8x=(2x+4)(2x+4)
4x² -8x=4x²+8x+8x+16
4x²-8x-4x²-16x=16
-24x=16/:(-24)
x=-16/24

b)
x(2x-1)= 2(x+2)²
2x² -x=2(x+2)(x+2)
2x²-x= 2(x²+2x+2x+4)
2x²-x=2x²+8x+8
2x²-x-2x²-8x=8
-9x=8/:(-9)
x=-8/9
2009-11-28T16:09:44+01:00
4x(x-2) = (2x+4)²
4x² - 8x = 4x² + 16x + 16
4x² - 8x - 4x² + 16x = 16
8x = 16 /: 8
x = 2

x(2x-1)= 2(x+2)²
2x² - x = 2(x² + 4x + 4)
2x² - x = 2x² + 8x + 8
2x² - x - 2x² - 8x = 8
-9x = 8 /:-9
x = - 8/9 ( w ułamku)
2009-11-28T16:17:22+01:00
4x(x-2)= (2x+4)²
4x² - 8x=(2x+4)(2x+4)
4x² -8x=4x²+8x+8x+16
4x²-8x-4x²-16x=16
-24x=16/:(-24)
x=-16/24
x=-1/2
x=-0,5

x(2x-1)= 2(x+2)²
2x² -x=2(x+2)(x+2)
2x²-x= 2(x²+2x+2x+4)
2x²-x=2x²+8x+8
2x²-x-2x²-8x=8
-9x=8/:(-9)
x=-8/9

możesz także przy potęgach zastosować wzór skroconego mnożenia (a+b)²=a²+2ab+b²